La biblioteca de la família Mercader de València l'any 1489 - Wittlin, Curt (Caplletra. Revista Internacional de Filologia, 1998)
From the inventory of books that Matias Mercader possessed, Wittlin raises doubts about the role of this family as cultural mentors proposed by several crítics, and in particular he qüestions the influence this library might have had on the literary and intellectual background of Joanot Martorell.